Group 2 innate lymphoid cells are key in lipid transfer protein allergy pathogenesis - Palomares, Francisca; Pérez-Sánchez, Natalia; Nieto, Nazaret; Núñez, Rafael; Cañas, José Antonio; Martín-Astorga, María del Carmen; Cruz-Amaya, Anyith; Torres, María José; Eguíluz-Gracia, Ibon; Mayorga, Cristobalina; Gómez, Francisca (Frontiers in Immunology, 2024)
Background Immunopathology in food allergy is characterized by an uncontrolled type 2 immune response and specific-IgE production. Recent studies have determined that group 2 innate lymphoid cells (ILC2) participate in the food allergy pathogenic mechanism and their severity. Our objective was to investigate the role of ILC2 in peach-allergic patients due to non-specific lipid transfer protein (Pru p 3) sensitization. Methods The immune response in peripheral blood mononuclear cells was characterized in lipid transfer protein-allergic patients and healthy controls. We have analyzed the Pru p 3 uptake on ILC2, the expression of costimulatory molecules, and their involvement on the T-cell proliferative response and cytokine production under different experimental conditions: cytokines involved in group 2 innate lymphoid cell activation (IL-33 and IL-25), Pru p 3 as main food allergen, and the combination of both components (IL-33/IL-25+Pru p 3) using cell sorting, EliSpot, flow cytometry, and confocal microscopy. Results Our results show that Pru p 3 allergen is taken up by group 2 innate lymphoid cells, regulating their costimulatory molecule expression (CD83 and HLA-DR) depending on the presence of Pru p 3 and its combination with IL-33/IL-25. The Pru p 3-stimulated ILC2 induced specific GATA3+Th2 proliferation and cytokine (IL-4, IL-5, and IL-13) production in lipid transfer protein-allergic patients in a cell contact-dependent manner with no changes in Tbet+Th1- and FOXP3+Treg cell differentiation. Conclusions The results indicate that in lipid transfer protein-allergic patients, the responsible allergen, Pru p 3, interacts with group 2 innate lymphoid cells, promoting a Th2 cell response. Our results might be of interest in vivo, as they show a role of group 2 innate lymphoid cells as antigen-presenting cells, contributing to the development of food allergy. Consequently, group 2 innate lymphoid cells may be considered as potential therapeutic targets.